2012
DOI: 10.1088/0004-637x/748/1/64
|View full text |Cite
|
Sign up to set email alerts
|

The Clustered Nature of Star Formation. Pre-Main-Sequence Clusters in the Star-Forming Region NGC 602/N90 in the Small Magellanic Cloud*

Abstract: Located at the tip of the wing of the Small Magellanic Cloud (SMC), the star-forming region NGC 602/N90 is characterized by the HII nebular ring N90 and the young cluster of pre-main-sequence (PMS) and earlytype main sequence stars NGC 602, located in the central area of the ring. We present a thorough cluster analysis of the stellar sample identified with HST/ACS camera in the region. We show that apart from the central cluster, low-mass PMS stars are congregated in thirteen additional small compact sub-clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…At least seven OB-type stars and numerous lower-mass stars reside in 'sub-cluster 1' (Gouliermis et al 2012), with the stellar density distribution comparable to the distribution of extended X-ray emission (see Fig. 4).…”
Section: Sub-cluster 1: the Core Of Ngc 602amentioning
confidence: 74%
See 1 more Smart Citation
“…At least seven OB-type stars and numerous lower-mass stars reside in 'sub-cluster 1' (Gouliermis et al 2012), with the stellar density distribution comparable to the distribution of extended X-ray emission (see Fig. 4).…”
Section: Sub-cluster 1: the Core Of Ngc 602amentioning
confidence: 74%
“…5). Gouliermis et al (2012) showed that NGC 602a is hierarchically structured, and identified sub-clusters that differ in age, mass, and size (their Table 1). Two of the areas of extended X-ray emission coincide with their two most populous sub-clusters (see Fig.…”
Section: Extended X-ray Emissionmentioning
confidence: 99%
“…Typically, the positions of the PMS stars in the CMD do not overlap with those of the main-sequence stars, and therefore it is quite straightforward for our field-subtraction technique to eliminate completely features that are typical of old populations from the original CMD (e.g., Gouliermis et al 2011Gouliermis et al , 2012. However, our field decontamination method is not optimized for regions of high differential extinction because evolved stars in such regions strongly contaminate the CMD positions of the PMS stars due to reddening.…”
Section: Identification Of the Pre-main-sequence Populationsmentioning
confidence: 99%
“…Numbers 1 through 4 indicate the positions of the regions whose properties are shown in Table 1. Table columns are as follows: ID number of the region; ID number as given by Gouliermis et al (2012); X and Y coordinates in Figure 8; number of actively accreting PMS stars younger than 5 Myr in the region; their median mass, median age, median Hα luminosity, and median bolometric luminosity. 8 µm.…”
Section: Younger Pms Starsmentioning
confidence: 99%